Maria Gołda-Sobczak "Krym jako przedmiot sporu ukraińsko-rosyjskiego" / Stanisław Wójcik. - Wójcik, Stanisław (1949- ).
Recenzja: Krym jako przedmiot sporu ukraińsko-rosyjskiego / Maria Gołda-Sobczak. - Poznań, 2016.